The value of national arthroplasty registry data in 2023. (15th March 2023) - Baker, Paul N.; Jeyapalan, Rathan; Jameson, Simon S.
Abstract : The importance of registries has been brought into focus by recent UK national reports focusing on implant (Cumberlege) and surgeon (Paterson) performance. National arthroplasty registries provide real-time, real-world information about implant, hospital, and surgeon performance and allow case identification in the event of product recall or adverse surgical outcomes. They are a valuable resource for research and service improvement given the volume of data recorded and the longitunidal nature of data collection. This review discusses the current value of registry data as it relates to both clinical practice and research. Cite this article: Bone Joint J 2023;105-B(4):356–360.